HUBUNGAN BERPIKIR KREATIF DAN KEMAMPUAN MEMBACA PEMAHAMAN DENGAN KEMAMPUAN MENULIS CERPEN SISWA KELAS V SEKOLAH DASAR STRADA BHAKTI NUSA - samino, francine avantie (Jurnal Pendidikan Dasar, 2018)
The objective of this research was to determine: the correlation between creative thinking and ability of reading comprehension with the ability of writing short stories through both separately and simultaneously. The study was conducted on SD Strada Bhakti Nusa Tangerang in 2015 with 40 samples taken by using simple total sampling. The technique used to analyze the data was the statistical technique of regression and correlation. The results of this research showed that there was a positive correlation between: (1) creative thinking with ability of reading comprehension, (2) ability of reading comprehension with ability of writing short stories, (3) creative thinking, ability of reading comprehension with ability of writing short stories. Based on the research results, it could be concluded that the ability of reading comprehension had a greater contribution to the ability of writing short stories compared with creative thinking. However, creative thinking and the ability of reading comprehension have contribution jointly to the ability to write short stories